Processing-Structure-Property Relationships in Metals - Montanari, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In the industrial manufacturing of metals, the achievement of products featuring desired characteristics always requires the control of process parameters in order to obtain a suitable microstructure. The strict relationship among process parameters, microstructure, and mechanical properties is a matter of interest in different areas, such as foundry, plastic forming, sintering, welding, etc., and regards both well-established and innovative processes. Nowadays, circular economy and sustainable technological development are dominant paradigms and impose an optimized use of resources, a lower energetic impact of industrial processes and new tasks for materials and products. In this frame, this Special Issue covers a broad range of research works and contains research and review papers.